College Students vs. Online Gaming: Academic Procrastination, Conscientiousness and Self-regulated Learning - Chani, Azzahra Jihan; Hadjam, M. Noor Rochman; Marissa, Aski; Tarigan, Avinanta; Damariyanti, Meta (Faculty of Psychology, Universitas Gadjah Mada, 2026)
As part of the education community, students are expected to achieve academic goals. However, they oftenengage in academic procrastination due to distractions such as online gaming. The purpose of this study was toempirically determine the extent to which conscientiousness and self-regulated learning predict the academicprocrastination of students who play online games. The participants (N=119) were undergraduate students, aged 18-25years old, who actively played online games for at least 10 hours per week. The research instruments used wereSchouwenburg’s academic procrastination scale, the NEO Five-Factor Inventory-3 (conscientiousness items), andFitriani’s self-regulated learning scale. The results showed that conscientiousness and self-regulated learningcontribute significantly to the reduction of academic procrastination among students (F=319.702; p < 0.01; R2=0.846),indicating that self-control and conscientiousness play a crucial role in student learning behavior.